Transmission Coefficient Analysis of Notched Shape Floating Breakwater Using Volume of Fluid Method: A Numerical Study - Ridlwan, Asfarur; Armono, Haryo Dwito; Rahmawati, Shade; Tuswan, Tuswan (Department of Naval Architecture - Diponegoro University, 2021)
As one of the coastal structures, breakwaters are built to protect the coastal area against waves. The current application of breakwaters is usually conventional breakwaters, such as the rubble mound type. Climate change, which causes tidal variations, sea level height, and unsuitable soil conditions that cause large structural loads, can be solved more economically by employing floating breakwater. In this study, numerical simulations will be conducted by exploring the optimum floating breakwater notched shapes from the Christensen experiment. The comparison of three proposed floating breakwater models, such as square notch (SQ), circular notch (CN), and triangular notch (VN), is compared with standard pontoon (RG) to optimize the transmission coefficient value is analyzed. Numerical simulations are conducted using Computational Fluid Dynamics (CFD) based on the VOF method with Flow 3D Software. Compared to the experimental study, the RG model's validation shows a good result with an error rate of 8.5%. The comparative results of the floating breakwater models are found that the smaller the transmission coefficient value, the more optimal the model. The SQ structure has the smallest transmission coefficient of 0.6248. It can be summarized that the SQ model is the most optimal floating breakwater structure.